THE PRODUCT MAPPING AND THE MARKET SEGMENTATION TO DETERMINE THE STRATEGY TO ENHANCE THE BUSINESS COMPETITION OF THE MEDAN STUDENTS - Ani Murwani Muhar; Audia Junita (Proceeding International Conference on Information Technology and Business, 2016)
The result of this research showed that the business activities carried out by the college students were grouped into five clusters. They were: a) agriculture, b) livestock, c) fashion, d) handicraft, and e) culinary. Referring to the clusters, the businessmen among college students did some important steps to get advantages. One of the important steps was mapping the conditions in each of the categories. The mapping is directed on the particular segments based on lifestyles, such as: business enterprising types, resident types, social types, and entertainer types. The strategic steps were in the form of series of the stages of the program or activity which were determined by SWOT analysis. Through this analysis, it is expected that the businessmen could hold and determine the competitive advantage so that they could be the leader in the market. Moreover, it also occurred on the businesses which were implemented by young businessmen from the educational institution. By involving the micro, small enterprise businessmen, the experts, and the local government officials, this research obtained someimportant data or input in formulating marketing strategies to enhance the competition of the businesses of the micro, small enterprise. This research used qualitative and quantitative approaches. The data collecting techniques were filling the questionnaire, conducting depth interview, and doing FGD. The businessmenamong the college students had strengths on the non-physical aspects such as motivation and independence. In addition, the problems on the relationship which had existed so far between suppliers and customers or consumers could also be the strength forthe businessmen among the college students. However, the college students also hadweaknesses. The weaknesseswere in the form of the minimal capital, the simple business management issues, and the current infrastructures to process the production. The college students felt that the campus wasavery potential market. Moreover, their market shareon products was also relatively high compared to the competitors in the market insidethe campus. In addition, the opportunities which were seen by the businessmen were: a) competition at campus couldrelatively be overcome by them, b) the support of government agencies and the campus itself, and c) the consultancy assistance of the campus due to the businesses which was carried out. Furthermore, the conditionwhich complicates their business development was about the problem of competitionon condition that the products would be soldespecially in markets outside the campus.KEY WORDSClusters, Segmentation, Strategy, Competition.